Sex & money : pleasures that leave you empty and grace that satisfies - Tripp, Paul David, 1950- (Wheaton, Illinois Crossway, 2013)
Explains that the world has gone mad for sex and money and that the insanity for these two chief pleasures can be overcome with God's word and the power of the gospel.
Sorry, but we've gone crazy -- The dangerous dichotomy -- So why do we do the things we do? -- The highest pleasure -- Sex: the big picture -- If sex is about worship, then it can't be just about you -- If sex is about relationship, then it can't be just about you -- If sex is about obedience, then it can't be just about you -- So where do we go from here? -- Money matters -- Treasure hunters -- Money is not the problem -- love is -- You can't take it with you -- Are you living like you're poor?
Includes index.
Includes bibliographical references and index.
Keywords: Sex -- Religious aspects -- Christianity; Money -- Religious aspects -- Christianity